Faktor-Faktor Yang Memengaruhi Pembelian Berulang: Produk, Harga, Promosi, Dan Layanan: Literature Review Perilaku Konsumen - Mawaddah Mawaddah; Dewi Rahayu; Salsabila Rahmasari; Angga Dutahatmaja (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
The current modern era brings various opportunities and new business opportunities. This causes more and more prospective entrepreneurs to be interested in taking advantage of existing infrastructure advances to support their business. Apart from that, it has an impact on increasing the level of competition in the industry, which can be indicated by the increasing number of competitors from similar companies that present alternative choices for consumers with different promotions and quality. In fact, each company has its own unique way of holding promotions to attract consumer attention. Therefore, entrepreneurs need to prioritize efforts to implement effective product quality, prices, promotions and services to maximize sales levels. This research is aimed at analyzing the influence of product quality, price, promotion and service on repeat purchase decisions. The approach is a qualitative approach, by collecting data through literature study from previous articles and literature. Research findings reveal that product quality, price, promotions, and service have a significant influence on repeat purchases by consumers. Satisfactory product quality and affordable prices can increase consumers' interest in repurchasing. Apart from that, attractive promotions and quality service also play an important role in influencing consumer satisfaction and encouraging repeat purchases.